2016
DOI: 10.1016/j.bjane.2013.06.021
|View full text |Cite
|
Sign up to set email alerts
|

Role of noninvasive ventilation in perioperative patients with neuromuscular disease: a clinical case

Abstract: The inclusion body myositis is an inflammatory myopathy that leads to chronic muscle inflammation associated with muscle weakness. It is characterized by a restrictive ventilatory syndrome requiring ventilatory support under non-invasive ventilation. The authors describe a clinical case and the anaesthetic management of a patient with inclusion body myopathy candidate for vertebroplasty, which highlights the importance of locoregional anaesthesia and of noninvasive ventilation and includes assisted cough techn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…Some published articles report the use of reduced doses or avoidance of muscle relaxants in patients with IBM because of the possibility of exaggerated sensitivity to these drugs and prolonged duration of action in inflammatory myopathies including IBM. 7 , 8 , 13 , 14 However, there are no conclusive data regarding the pharmacokinetics, pharmacodynamics, and safety of neuromuscular blockers in IBM. In fact, the case series by Mortenson et al reported 16 patients with IBM who underwent surgery and received either depolarizing or nondepolarizing agents.…”
Section: Discussionmentioning
confidence: 99%
“…Some published articles report the use of reduced doses or avoidance of muscle relaxants in patients with IBM because of the possibility of exaggerated sensitivity to these drugs and prolonged duration of action in inflammatory myopathies including IBM. 7 , 8 , 13 , 14 However, there are no conclusive data regarding the pharmacokinetics, pharmacodynamics, and safety of neuromuscular blockers in IBM. In fact, the case series by Mortenson et al reported 16 patients with IBM who underwent surgery and received either depolarizing or nondepolarizing agents.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, he did not develop aspiration pneumonia after surgery. Marinho et al reported a unique approach to anesthesia in a patient with IBM who underwent percutaneous thoracic vertebral kyphoplasty in prone position ( 23 ). This patient required chronic non-invasive ventilation because of poor respiratory function.…”
Section: Discussionmentioning
confidence: 99%
“…The patient’s intraoperative care was managed using epidural anesthesia, conscious sedation, and bi-level positive airway pressure. In this case, the authors ( 23 ) avoided endotracheal intubation entirely because they were concerned that the patient’s preexisting respiratory dysfunction may preclude their ability to wean the patient from mechanical ventilation after the procedure.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation